DESAIN ALAT BANTU PROSES PEMOTONGAN TAHU GUNA MENINGKATKAN PRODUKTIVITAS PRODUKSI - bidiawati, ayu; Muchtiar, Yesmizarti; Setiawati, Lestari; Suherman, Hendra; Desmiarti, Reni (Fakultas teknik Universitas Muhammadiyah Jakarta, 2024)
A company in the food industry that produces tofu has encountered issues with product size inconsistency in each batch. This is due to the very basic cutting process currently using only a knife and a wooden roller. As a result, errors can occur during production, leading to tofu pieces that are not uniform in size. To address this, a design for a cutting aid has been developed to increase the number of cut pieces and minimize the cutting process time. This cutting aid was designed using a rational method. The tofu cutting aid is ergonomically designed to make it easier for workers to perform their tasks. The goal of this tool is to produce tofu pieces that are uniform and of the same shape.